Analisis Perbandingan Kinerja Antara Sensor Api Flame 5 Channel Dengan Sensor Asap MQ2 - Masesa Angga Wijaya; Rokhmat Nur Ikhsan; Egi Sugianto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Sensors are devices used to detect changes in physical quantities such as light, motion, fire, humidity, temperature, smoke and other environmental phenomena. With the use of sensors, changes in the environment that are detected by the sensor can be seen. Each sensor has a different function but can be used for the same purpose, for example, in detecting a fire. A fire incident can be identified by two things, namely the presence of fire or smoke, but it cannot be known whether it is fire or smoke first which is easy to detect from the fire. Therefore it is necessary to do a sensor performance comparison test which aims to find out which sensor detects fire earlier. This study uses a quantitative two-sensor test comparison method. The two sensors, namely the Flame 5 Channel fire sensor, have a function to detect fire which will be tested with the time parameter needed to detect fire based on the distance and the fan's time requirement to turn off the fire. Then the MQ2 sensor has a function to detect smoke based on its thickness which will be tested with the estimated time parameter for the thickness of the smoke until the sensor detects it based on the distance and time it takes for the smoke to disappear using a fan. The results of this study are a comparison of the two sensor tests to become a recommendation for the use of sensors in detecting fires.